2015
DOI: 10.1177/0884533615621549
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intracellular Water Following Hemodialysis Treatment Lead to Changes in Estimates of Lean Tissue Using Bioimpedance Spectroscopy

Abstract: In clinical practice, predialysis bioimpedance measurements are more convenient. However, for more reliable and reproducible assessments of nutrition status, we suggest that measurements of body composition should be made when patients are not overhydrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…We did not find any association between higher scores and loss of muscle mass. We measured muscle mass by bioimpedance, 32 and previous studies have reported differences using bioimpedance devices in HD patients, 7 , 33 and even though we allowed for reequilibration following the dialysis session, 34 further studies using DXA 35 or isotopic methods may be required to confirm our results.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We did not find any association between higher scores and loss of muscle mass. We measured muscle mass by bioimpedance, 32 and previous studies have reported differences using bioimpedance devices in HD patients, 7 , 33 and even though we allowed for reequilibration following the dialysis session, 34 further studies using DXA 35 or isotopic methods may be required to confirm our results.…”
Section: Discussionmentioning
confidence: 85%
“…As HD patient survival is reduced in cases of both muscle weakness and wasting, rapid screening tests are useful to detect muscle weakness and wasting at an early stage. Although dual‐energy x‐ray absorptiometry (DXA) and bioimpedance methods can be used to assess lean body mass (LBM), 4 , 5 these methods may overestimate LBM in patients who are overhydrated 6 , 7 . As such, many kidney dialysis centers use handgrip strength (HGS) as a functional assessment of muscle weakness, 8 which can be readily tested when patients attend for dialysis sessions or in the outpatient clinic.…”
mentioning
confidence: 99%
“…In addition, the noninvasive nature of bioimpedance makes it particularly well suited for measuring longitudinal changes. Notably, BIS techniques have recently shown promise in assessing body composition and mortality risk in people on dialysis 81 and in managing fluid status in dialysis 88 93 as well as surgery 92 and critically illness 91 …”
Section: Bioimpedancementioning
confidence: 99%
“…As muscle contains more water than fat, this leads to an overestimation of lean body mass pre dialysis, with a reduction in lean body mass post dialysis [24] . More recently, a three-compartmental body composition model has been proposed, dividing the body into adipose tissues, normally hydrated lean tissue and excess water, but even this model still overestimates lean body mass pre dialysis [25] . We measured bioimpedance post dialysis after allowing for a redistribution of fluid to overcome these effects on bioimpedance measurements.…”
Section: Discussionmentioning
confidence: 99%